Exploring the adoption rationales and effects of off-grid renewable energy access for African youth: a case study from Tanzania - Rabenold, Colton (University of Cape Town, 2020)
In addition to being one of the poorest countries in Africa, Tanzania is considered the 13th most vulnerable nation in the world to climate change and climate variability. Currently over 63% of Tanzanians have no access to the national power grid. Instead they rely on biomass and kerosene lamps to provide energy in their homes. In addition, rural youth in Tanzania have limited occupational pursuits other than subsistence farming (both formal and informal). Utilizing a case study approach, this research qualitatively explores the effects of energy access in the form of solar PV for those seeking to secure this public good at a household-level. Face-to-face interviews conducted in the coastal region of Tanzania concentrated on understanding rationales for adopting off-grid energy (adoption rationales), particularly respondent's 'Awareness', 'Motivation' and selected 'Pathways' (the AMP Framework). High rates of rural poverty highlight systemic lack of energy access in Tanzania. In contrast, livelihood transformations through solar PV were observed in the case to couple with energy access. Indicators of improvement in living standards were observed to have cascading influence on other adopters which, in turn, encouraged further uptake. This innovative adoption lead to decreased pressure on the surrounding ecosystems, but environmental factors did not influence initial adoption rationales. Reflecting on the findings, the author develops a framework for better understanding of the role private actors take in transitions from to off-grid energy access in Africa. Reflecting on the case observations, particularly how respondents sought shape the flow of events independent, and sometimes in spite of, the State, the framework extends current understandings of nodes of change in rural communities and provides a more extensive exploration of behavioural theories (the AMP Framework and Diffusion Theory). Novel connections are made conceptually with emerging nodes of change and decision-making theories of change to provide fresh extension of these approaches to understanding poverty arrangements in Africa and what researchers and decision makers might need to consider for targeted interventions towards universal energy access on the continent. The thesis concludes with a range of principles for energy access in Africa distilled from the observations and framework developed. They include environmental principles of sustainable resource management and socioecological balance, social principles of equality and participation, and economic principles of access and stability.